Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Cities are hotspots for threatened species - Christopher D. Ives; Pia E. Lentini; Caragh G. Threlfall; Karen Ikin; Danielle F. Shanahan; Georgia E. Garrard; Sarah A. Bekessy; Richard A. Fuller; Laura Mumaw; Laura Rayner; Ross Rowe; Leonie E. Valentine; et al. (Global Ecology and Biogeography, 2016)
Aim Although urbanization impacts many species, there is little information on the patterns of occurrences of threatened species in urban relative to non‐urban areas. By assessing the extent of the distribution of threatened species across all A ustralian cities, we aim to investigate the currently under‐utilized opportunity that cities present for national biodiversity conservation. Location A ustralian mainland, T asmania and offshore islands. Methods Distributions of A ustralia's 1643 legally protected terrestrial species (hereafter ‘threatened species’) were compiled. We assessed the extent to which they overlapped with 99 cities (of more than 10,000 people), with all non‐urban areas, and with simulated ‘dummy’ cities which covered the same area and bioregion as the true cities but were non‐urban. We analysed differences between animals and plants, and examined variability within these groups using species accumulation modelling. Threatened species richness of true versus dummy cities was analysed using generalized linear mixed‐effects models. Results A ustralian cities support substantially more nationally threatened animal and plant species than all other non‐urban areas on a unit‐area basis. Thirty per cent of threatened species were found to occur in cities. Distribution patterns differed between plants and animals: individual threatened plant species were generally found in fewer cities than threatened animal species, yet plants were more likely to have a greater proportion of their distribution in urban areas than animals. Individual cities tended to contain unique suites of threatened species, especially threatened plants. The analysis of true versus dummy cities demonstrated that, even after accounting for factors such as net primary productivity and distance to the coast, cities still consistently supported a greater number of threatened species. Main conclusions This research highlights that A ustralian cities are important for the conservation of threatened species, and that the species assemblages of individual cities are relatively distinct. National conservation policy should recognize that cities play an integral role when planning for and managing threatened species.

Guidelines for Using Movement Science to Inform Biodiversity Policy - Philip S. Barton; Pia E. Lentini; Erika Alacs; Sana Bau; Yvonne M. Buckley; Emma L. Burns; Don A. Driscoll; Lydia K. Guja; Heini Kujala; José J. Lahoz-Monfort; Alessio Mortelliti; Ran Nathan; et al. (Environmental Management, 2015)

The response of faunal biodiversity to an unmarked road in the Western Amazon - Andrew Whitworth; Christopher Beirne; Jasmine Rowe; Fraser Ross; Caroline Acton; Oliver Burdekin; Philip Brown (Biodiversity and Conservation, 2015)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Utilizing the frost resistance of diploid solanum species - R. W. Ross; P. R. Rowe (American Journal of Potato Research, 1969)

Frost resistance among theSolanum species in the ir-1 potato collection - R. W. Ross; P. R. Rowe (American Journal of Potato Research, 1965)